Excess mortality in England and Wales, and in Greater London, during the 1995 heatwave. Issue 8 (August 1998) - Rooney, C; McMichael, A J; Kovats, R S; Coleman, M P
Abstract : STUDY OBJECTIVE: To assess the impact on mortality of the heatwave in England and Wales during July and August 1995 and to describe any difference in mortality impact between the Greater London urban population and the national population. DESIGN: Analysis of variation in daily mortality in England and Wales and in Greater London during a five day heatwave in July and August 1995, by age, sex, and cause. SETTING: England and Wales, and Greater London. MAIN RESULTS: An estimated 619 extra deaths (8.9% increase, approximate 95% confidence interval 6.4, 11.3%) were observed during this heatwave in England and Wales, relative to the expected number of deaths based on the 31-day moving average for that period. Excess deaths were apparent in all age groups, most noticeably in women and for deaths from respiratory and cerebrovascular disease. Using published daily mortality risk coefficients for air pollutants in London, it was estimated that up to 62% of the excess mortality in England and Wales during the heatwave may be attributable to concurrent increases in air pollution. In Greater London itself, where daytime temperatures were higher (and with lesser falls at night), mortality increased by 16.1% during the heatwave. Using the same risk coefficients to estimate the excess mortality apparently attributable to air pollution, more than 60% of the total excess in London was apparently attributable to the effects of heat. CONCLUSION: Analysis of this episode shows that exceptionally high temperatures in England and Wales, though rare, do cause increases in daily mortality.